Accounting Information System and Environmental Uncertainty among Agri-Related Cooperatives in Davao del Norte - Flores, Joe Mari N.; Baguio, Cristen Ge P.; Idul, Frances Joy M.; Llemit, Maria Ella M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The primary purpose of this study was to explore the relationship between the variables covered in this study - the Accounting Information System and environmental uncertainty among agri-related cooperatives- and provide personal knowledge and a framework for the contingency theory. The research advocates that most entities need to modernize their business operations due to the emergence of technological advances to support organizational change and decision-making. The study's findings aim to benefit agri-related cooperatives, such as the Board of Directors, the Management, the Entrepreneurs, and future researchers seeking insights. The study focused on agri-related cooperatives in Davao del Norte, targeting accountants or bookkeepers. The selection of respondents was made in a complete enumeration involving seventy-four (74) respondents for the survey as per the data provided by the Cooperative Development Authority. The methodology aims for more reliable insights into the Accounting Information System and environmental uncertainty representing the agri-related cooperative sector. The findings indicate that adequately using a reliable Accounting Information System helps businesses deal with uncertainties. However, the greater the likelihood of environmental uncertainty, the greater the possibility that the Accounting Information System is unlikely to capture operational issues useful for decision-making. Thus, this study concludes that the Agri-related cooperatives in Davao del Norte are highly uncertain, and the usage of the Accounting Information system did not significantly affect the decision-making process.